Advective Lateral Transport of Streamwise Momentum Governs Mixing at Small River Confluences. Issue 9 (10th September 2020) - Lewis, Quinn; Rhoads, Bruce; Sukhodolov, Alexander; Constantinescu, George
Abstract: Confluences are important sites for mixing within river networks. Past work has shown that mixing within confluences is highly variable; in some cases flows mix rapidly and in other cases flows remain unmixed far downstream of the confluence. The fluvial processes that govern mixing within confluences remain poorly understood. This study relates patterns and amounts of mixing to three‐dimensional flow structure at three small confluences. It focuses on lateral fluxes of streamwise momentum, which theoretical considerations suggest should influence lateral mixing. Patterns and amounts of mixing differ at the three sites. Considerable mixing occurs at an asymmetrical confluence with strong helical motion within flow from the lateral tributary, which produces substantial differences in advective lateral transport of streamwise momentum over depth. Minor mixing occurs at a comparatively symmetrical confluence where incoming flows have relatively equal momentum fluxes; however, helical motion within one of the flows locally increases mixing. At a symmetrical confluence where one incoming flow has much greater momentum flux than the other, mixing occurs largely through progressive lateral shifting of the mixing interface toward the minor tributary because of the strong lateral flux of streamwise momentum by the dominant tributary. At all three confluences, lateral turbulent transport of streamwise momentum is an order of magnitude less than advective lateral transport of streamwise momentum. The study indicates that generalization of mixing at confluences remains challenging but that advective lateral fluxes of streamwise momentum related to secondary currents (helical motion) or primary flow (cross currents) greatly enhance mixing at confluences. Key Points: Mixing within three small confluences is greatest when channel‐scale secondary flow is persistent and large in spatial extent Mixing rates are positively correlated to elevated magnitudes of lateral transport of streamwise momentum by secondary flow Rapid mixing is most likely to occur at a high‐angle asymmetrical confluence with a momentum flux ratio greater than 1